2017
DOI: 10.1021/acs.accounts.7b00300
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Iridium-Catalyzed Asymmetric Allylic Substitution Reactions in Target-Oriented Synthesis

Abstract: Metal catalyzed allylic substitution is a cornerstone of organometallic and synthetic chemistry. Enantioselective versions have been developed with catalysts derived from transition metals, most notably molybdenum, nickel, ruthenium, rhodium, iridium, palladium, and copper. The palladium- and the iridium-catalyzed versions have turned out to be particularly versatile in organic synthesis because of the very broad scope of the nucleophile and great functional group compatibility. Assets of the iridium-catalyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(83 citation statements)
references
References 68 publications
1
82
0
Order By: Relevance
“…[7e, 11] Gratifyingly,when Yb(OTf) 3 , In(OTf) 3 ,a nd Fe(OTf) 2 were tested, the reactions worked better,a ffording 3a in 58-70 %y ields.N ext, as eries of solvents were evaluated with Fe(OTf) 2 as the promoter, and DCE was identified as the optimal choice (entries [6][7][8][9]. With an Ir complex derived from [Ir(cod)Cl] 2 (3 mol %) and the Carreira (P,o lefin) ligand (S)-L1 (12 mol %) as the catalyst, and diphenylsulfonimide as the promoter for the electrophile,the reaction proceeded in 1,2-dichloroethane (DCE) and afforded the desired product 3a in 30 %yield (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7e, 11] Gratifyingly,when Yb(OTf) 3 , In(OTf) 3 ,a nd Fe(OTf) 2 were tested, the reactions worked better,a ffording 3a in 58-70 %y ields.N ext, as eries of solvents were evaluated with Fe(OTf) 2 as the promoter, and DCE was identified as the optimal choice (entries [6][7][8][9]. With an Ir complex derived from [Ir(cod)Cl] 2 (3 mol %) and the Carreira (P,o lefin) ligand (S)-L1 (12 mol %) as the catalyst, and diphenylsulfonimide as the promoter for the electrophile,the reaction proceeded in 1,2-dichloroethane (DCE) and afforded the desired product 3a in 30 %yield (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…[7] Notably,i n2 014, the group of Carreira reported highly enantioselective allylic substitution reactions of branch cinnamyl alcohols with 1,1-disubstituted olefins using achiral Ir-(P,olefin) complex. [7] Notably,i n2 014, the group of Carreira reported highly enantioselective allylic substitution reactions of branch cinnamyl alcohols with 1,1-disubstituted olefins using achiral Ir-(P,olefin) complex.…”
Section: Introductionmentioning
confidence: 99%
“…Iridium-catalyzed allylic amination has emerged as an important method for enantioselective C À N bond formation. [1][2][3][4][5][6][7][8][9] Pursuant to the pioneering work of Takeuchi, [1,2] studies from the laboratories of Helmchen, [3,4] Hartwig, [5,6] Carreira, [7] and You [8,9] have shown that chiral phosphoramidite-modified iridium complexes are especially effective in this regard (Figure 1). Like the parent palladium-catalyzed Tsuji-Trost reactions, [10] the iridium-phosphoramidite-catalyzed allylic alkylations occur via cationic p-allylmetal intermediates.Recently,wefound that p-allyliridium-C,O-benzoates,w hich are wellknown to promote nucleophilic allylation of carbonyl compounds, [11,12] are also effective catalysts for highly regio-and enantioselective electrophilic allylation of amines.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Pursuant to the pioneering work of Takeuchi, [1,2] studies from the laboratories of Helmchen, [3,4] Hartwig, [5,6] Carreira, [7] and You [8,9] have shown that chiral phosphoramidite-modified iridium complexes are especially effective in this regard ( Figure 1). [1][2][3][4][5][6][7][8][9] Pursuant to the pioneering work of Takeuchi, [1,2] studies from the laboratories of Helmchen, [3,4] Hartwig, [5,6] Carreira, [7] and You [8,9] have shown that chiral phosphoramidite-modified iridium complexes are especially effective in this regard ( Figure 1).…”
mentioning
confidence: 99%